The Y‐TiO2/5A/NiFe2O4 Composite for the High‐efficiency Adsorption and Photocatalytic Degradation of Norfloxacin under Visible Light. Issue 29 (2nd August 2021) - Xu, Jing; Ren, Zhihao; Qiu, Xiaoyuan; Zhu, Pengfei; Chen, Dandan; Xie, Lisi; Zhang, Chaoli
Abstract: Y‐TiO2 /5A/NiFe2 O4 composite was prepared by hydrothermal and sol‐gel method. The structure, morphology and optical properties of the composite were investigated by XRD, FT‐IR, XPS, SEM, UV‐vis DRS and so on. Compared with 5A, TiO2, TiO2 /5A and Y‐TiO2 /5A, the photocatalytic properties of Y‐TiO2 /5A/NiFe2 O4 was enhanced and the removal rate of norfloxacin can reach the highest 96.55 % under visible light for 60 min. Moreover, the photocatalyst still has good photocatalytic performance after three cycles of use. This improvement is mainly attributed to two factors. On the one hand, the doping of Y brings impurity level to TiO2, which broadens the spectral response range of the photocatalyst to the visible region. On the other hand, NiFe2 O4 forms Z‐scheme heterojunction with TiO2, which enables the photogenerated carriers to be separated effectively through the interface of heterojunction, thus improving the performance of the photocatalyst. Moreover, the photocatalyst still has a good removal rate for several other antibiotics. Finally, a possible electron transfer mechanism is proposed based on characterization and active species capture experiments. Abstract : Rare earth Y doping introduced the impurity level in TiO2, which expanded the spectral response range of the catalyst. Moreover, NiFe2 O4 and TiO2 combine to form heterojunction, which enables the photogenerated electrons to be transferred through Z‐scheme electron transfer mechanism and separated electron‐hole pairs effectively, thus significantly improving the photocatalytic activity.